SEED SOWING ORIENTATION RELATED TO SEED COAT ADHERENCE ON WATERMELON - Dias, Marcos Altomani Neves; Sugianto, Dial; Guner, Nihat; Hassan, Mohammed (REVISTA DE AGRICULTURA, 2013)
Watermelon (Citrullus lanatus (Thunb.) Matsum & Nakai) seedlings generally present issues regarding to seed coat adherence to cotyledons at the emergence stage. In this case, the seed coat acts as a barrier for seedling development, which may result in stretched or malformed seedlings. Therewith, this study was carried out to evaluate the effects of seed orientation in the substrate on seedling emergence and growth, and also to evaluate the effect on seed coat adherence. Diploid, triploid and tetraploid watermelon seeds were used in this study. The treatments were composed of four seed lots and three different seed orientations at sowing: hilum pointed upwards (HUp), hilum pointed downwards (HDown) and hilum pointed horizontally (HHor). The evaluations consisted of: seedling emergence, seedling speed index, seedling height, seedling dry mass and seed coat adherence to cotyledons. HUp presented lower results for seed coat adherence to cotyledons, but negatively interfered on seedlings emergence and growth.Â  In general, the treatment HHor presented the most satisfactory results, even though it did not solve the seed coat adherence issue.